Copper wire characterisation for fire source determination - Mesrun, Norlyiana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Electrical fire is a fire started by electrical means. During investigation, fire investigators need to prove the cause of these fires if the cases involve electrical failures or mal functions. Therefore, this study focused on the characterisation of copper wire for fire source determination to provide an insight on the feature damage patterns between external flame burnt wires and electrically burnt wires. In this study, two different manufactured electrical wires, which were yellow and red insulated copper wire samples, were subjected to external flame and electrical overcurrent conditions. Different intensities of simulated fire conditions, namely instant, slightly and severely heated were introduced to the samples. Through microscopic examination, the cross sectional morphological features between insulated copper wire burnt by external flame and electrical overcurrent condition were distinct. However, this method was not reliable enough to be applied in real bumt cases where most electrical wiring were completely burnt, making the cross sectional features hard to be examined. The application of Fourier Transform Infra-red technique on the polymeric insulator of the wire samples showed slightly varying spectra through visual observation on the basis of simulated fire conditions. Principal Component Analysis of the burnt insulators provided an objective characterisation where the source of fire, either external flame or electrical means could be distinguished. The results have signaled the high potential of the technique as a tool for fire source determination. In conclusion, the study could help differentiate and characterise burnt wires based on their fire source. The findings provided information for forensic analyses and also aided the fire investigation. especially on electrical tire cases.